MLTI-01. IMMUNOLOGICAL REPROGRAMMING IN THE CNS TUMOR MICROENVIRONMENT AND THERAPEUTIC EFFICACY OF RADIOTHERAPY WITH STAT3 BLOCKADE. (12th August 2019) - Ott, Martina; Hashimoto, Yuuri; Marisetty, Anantha; Wei, Jun; Zamler, Daniel; Leu, Jia-Shiun; Kong, Ling-Yuan; Zhou, Shouhao; Fuller, Gregory; de Groot, John; Priebe, Waldemar; Sulman, Erik; et al.
Abstract: BACKGROUND: Patients with central nervous system (CNS) tumors are typically treated with radiation therapy, but this is not curative and results in the upregulation of p-STAT3 that drives invasion, angiogenesis, and immune suppression. Therefore, we investigated the combined effect of an inhibitor of the STAT3 pathway that is currently in clinical trials (WP1066) and whole-brain radiation therapy (WBRT) in murine models of CNS malignancy. METHODS: C57BL/6 mice underwent intracerebral implantation of either B16 melanoma or GL261 glioma cells, WBRT, and treatment with WP1066 a blood-brain barrier penetrant inhibitor of the STAT3 pathway or the two in combination. The role of the immune system was evaluated using tumor rechallenge strategies, immune incompetent backgrounds, immune monitoring, and nanostring gene expression analysis of 770 immune-related genes from immune cells, including those directly isolated from the CNS tumor microenvironment. RESULTS: The combination of WP1066 and WBRT resulted in long-term survivors and enhanced median survival time relative to monotherapy. Immunological memory appeared to be induced, because mice were protected during subsequent tumor rechallenge. Therapeutic efficacy was completely lost in immune incompetent mice. Extensive functional immune monitoring and nanostring profiling followed by bioinformatic processing revealed that the most robust immunological responses were located in the CNS tumor microenvironment rather than the periphery. An unbiased analysis of the immune-cell heat maps of the combination therapy relative to monotherapy were notable for upregulation of T-cell functional genes, dendritic cell function, MHC expression, and antigen presentation in the CNS tumor. These data highly suggest that antigen presentation and T-cell effector function are requirements within the tumor microenvironment of the CNS for full antitumor immune-mediated activities. CONCLUSION: This study indicates that the combination of STAT3 inhibition and WBRT enhances the therapeutic effect against established tumors in the CNS by inducing dendritic cell maturation and activation in the CNS tumor.